Recent Progress of Rational Modified Nanocarriers for Cytosolic Protein Delivery - Xiao He; Su Xiong; Yansun Sun; Min Zhong; Nianting Xiao; Ziwei Zhou; Ting Wang; Yaqin Tang; Jing Xie (MDPI AG, 2023)
Therapeutic proteins garnered significant attention in the field of disease treatment. In comparison to small molecule drugs, protein therapies offer distinct advantages, including high potency, specificity, low toxicity, and reduced carcinogenicity, even at minimal concentrations. However, the full potential of protein therapy is limited by inherent challenges such as large molecular size, delicate tertiary structure, and poor membrane penetration, resulting in inefficient intracellular delivery into target cells. To address these challenges and enhance the clinical applications of protein therapies, various protein-loaded nanocarriers with tailored modifications were developed, including liposomes, exosomes, polymeric nanoparticles, and nanomotors. Despite these advancements, many of these strategies encounter significant issues such as entrapment within endosomes, leading to low therapeutic efficiency. In this review, we extensively discussed diverse strategies for the rational design of nanocarriers, aiming to overcome these limitations. Additionally, we presented a forward-looking viewpoint on the innovative generation of delivery systems specifically tailored for protein-based therapies. Our intention was to offer theoretical and technical support for the development and enhancement of nanocarriers capable of facilitating cytosolic protein delivery.